Analisis Peran Guru PAI dalam Upaya Meningkatkan Motivasi Belajar Siswa - Burhanuddin Chusnul Chuluq; Maryadi Maryadi (Universitas Islam Negeri Walisongo, 2022)
Teachers have an important role in children's self-development by providing various kinds of knowledge and skills. So teachers are required to prepare various abilities in carrying out education and guidance to students by encouraging them to be independent in reaching maturity. The teacher's role can use various ways to generate learning motivation in students by doing: a) giving points, prizes, competitions, ego-involvement, giving tests, knowing results, praise, punishment, desire to learn, interests, and recognized goals. According to Abraham Maslow